2018
DOI: 10.1002/pbc.27100
|View full text |Cite
|
Sign up to set email alerts
|

Testing physical function in children undergoing intense cancer treatment—a RESPECT feasibility study

Abstract: Children with cancer are generally motivated to participate in physical function tests. Future studies should address diagnosis specific obstacles and design testing modalities that facilitate physical function tests in this target group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
0
24
0
1
Order By: Relevance
“…While posturography was only performed after medical treatment, two studies conducted balance tests during treatment. 114 , 148 Bone tumor patients were only included in one study, 103 while CNS cancer cohorts were the population of main interest. In terms of age, a wide spectrum including very young children, as well as older adult survivors of childhood cancer (up to an age of 63 years) were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…While posturography was only performed after medical treatment, two studies conducted balance tests during treatment. 114 , 148 Bone tumor patients were only included in one study, 103 while CNS cancer cohorts were the population of main interest. In terms of age, a wide spectrum including very young children, as well as older adult survivors of childhood cancer (up to an age of 63 years) were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Our intervention was likely to be too early, at least without supervision and personalized guidance, which might be one reason for poor fidelity. Nonetheless, recent evidence is reasoning early PA interventions since Nielsen et al found 24% reduction at 3 months in physical function in children with ALL [18]. Motivating children to be physically active from the beginning of the treatment with the existing resources remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptability of the intervention was evaluated based on Bowen et al [17] and similarly than Nielsen et al [18] by reporting the participation rate from the eligible patients and by reporting the retention rate of the participants during follow-up. We also gained information about the acceptability from the interviews.…”
Section: Methodsmentioning
confidence: 99%
“…The INTERACT study is a national multicenter, two-arm parallel-group, randomized controlled superiority trial based on empirical evidence within the research group ( 13 , 18 , 43 , 62 ) and methodical recommendations from current evidence ( 27 ). The primary endpoint is at 6 months after inclusion, and follow-up will be 12 months after ended treatment.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Further, it is based on several years of experience with exercising children and adolescents with cancer through the RESPECT project (REhabilitation including Social and Physical activity and Education in Children and Teenagers with cancer), based at Copenhagen University Hospital, Rigshospitalet. The RESPECT project has shown how children can and will perform safe, in-hospital exercise and how this counteracts side effects resulting from cancer treatment, including loss of fitness and muscle strength, compared with children in pediatric wards in other Danish hospitals ( 13 , 18 , 29 , 43 ). Two key principles of RESPECT are early rehabilitation from treatment initiation and supervised exercise, hypothesizing that: (1) Maintaining children's physical function and fitness is easier during treatment than recovering deficits and developing new relationships post-treatment and (2) supervised exercise is more effective than unsupervised exercise.…”
Section: Methods and Analysismentioning
confidence: 99%